Effectiveness of Integrated Interactive Problem Based Learning E-Modules in Improving Critical Thinking Abilities - Hamidah, Afreni; Hawalya, Hawalya; Sanjaya, M. Erick (Jurnal Paedagogy, 2024)
This study aims to analyze the improvement of students' critical thinking skills by using interactive modules integrated with problem-based learning on the excretory system material. The research method used pra experimental research design with a One-Shot Case Study. The data collection instrument was critical thinking ability test questions analyzed using SPSS version 27 software. The results showed a significant value for the T-test of 0.000 (<0.05), with an average N-gain score of 0.63, meaning there was a significant difference. The results of critical thinking abilities before and after using the PBL integrated interactive e-module with a significant increase of 0.63 (medium). So it is concluded that the PBL integrated interactive e-module is feasible, practical, and effective for improving students' critical thinking skills in studying biology on excretory system material.